INVESTIGATION OF THE EFFECT OF BASALT FIBER ON SELF-COMPACTING CONCRETE - Ozodabas, Aylin (International Journal of Research -GRANTHAALAYAH, 2018)
Self-compacting concrete is used in many application fields in construction, repair, and maintenance, and reinforcement. Self-settling concretes are advantageous in terms of labor and speed. Self-compacting concrete samples compared to the amount of binder; blast furnace slag 10 % and 30 %, plasticizer additive 2.7 %, basalt fiber 1.6 % in samples A and 3.2% in samples B were used. But basalt fiber was not used in samples C. The plasticizing additive used was kept constant in all samples. Slump Flow Test, V-funnel, L-box, compressive strength, ultrasonic pulse velocity, water absorption and weight per unit of volume tests were performed and the obtained values were discussed in detail in the discussion and conclusion sections. It has been observed that the use of basalt fiber reduces the workability in fresh concrete but increased the compressive strength values. Samples basalt containing could not provide determined standard values for slump flow and V-funnel and L-box tests. As the use of basalt fiber increased, the viscosity in the concrete decreased. For the samples with 1% basalt fiber, the pressure strength values decreased by 0.5% compared to the samples with basalt fiber.